Heart fitness for life : the essential guide to preventing and reversing heart disease - McGowan, Mary P., 1959- (Oxford University Press, 1997)
In this groundbreaking volume, Dr. Mary McGowan draws on her years of clinical experience to offer the first comprehensive approach to preventing and reversing cardiac disease - a proven, livable program that works. Of course, we can't change our age or our family history - but there are significant positive actions that we can take to change our lives without feeling deprived. And, at the core of Heart Fitness for Life are the stories of nine patients, ordinary men at women, who took on the challenge of fighting heart disease with Dr. McGowan's program - and who have won extraordinary victories. At last, in one volume, you have all the expert advice and information you need to truly live well, whether you are a man or a woman, looking to prevent or reverse cardiac disease. By covering all aspects of having a healthy heart, from diet and exercise to medication and estrogen replacement therapy, Dr. McGowan's book truly has the power to change your life.